The Assessment of Tp-e Interval and Tp-e/QT Ratio in Patients With Systemic Sclerosis - Çağrı YAYLA,; Müçteba Enes YAYLA,; Kadriye GAYRETLİ YAYLA,; Ufuk İLGEN,; Mehmet Kadri AKBOĞA,; Nurşen DÜZGÜN, (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate ventricular repolarization using T-peak to T-end (Tp-e) intervals and Tp-e/QT ratios in patients with systemic sclerosis (SSc). Patients and methods: Totally 65 patients (8 males, 57 females; mean age 49.8 years; range 20 to 77 years) with SSc and 63 control subjects (8 males, 55 females; mean age 49.3 years; range 20 to 77 years) were enrolled. Tp-e intervals, Tp-e/QT, and Tp-e/corrected QT (QTc) ratios were measured from the 12-lead electrocardiogram. Results: Tp-e intervals, QT intervals, QTc intervals, Tp-e/QT, and Tp-e/QTc ratios were significantly higher in patients with SSc than control subjects (all p<0.01). There was no difference between patients with diffuse and limited cutaneous SSc in terms of electrocardiogram and echocardiographic findings. Correlation analysis revealed no correlation between Tp-e intervals, Tp-e/QT, and Tp-e/QTc ratios with disease duration and anti-Sjögren’s syndrome antigen A antibody levels in patients with SSc (all p>0.05). Conclusion: Our study showed that Tp-e intervals, Tp-e/QT, and Tp-e/QTc ratios were increased in patients with SSc than control subjects. The increased frequency of ventricular arrhythmias can be clarified by increased indexes of ventricular repolarization parameters in patients with SSc.